Penerapan Metode Peramalan dalam Menyusun anggaran Penjualan dan Anggaran Produksi Sebagai Dasar Penyusunan Anggaran Biaya Produksi pada LAF Project - Raisya Putri Septianti; Neneng Dahtiah (Indonesian Accounting Literacy Journal, 2021)
This research was carried out in the LAF project, which is an MSME dedicated to production and commerce, to understand the application of sales forecasts in preparing sales budgets and production budgets, as the basis for preparing production cost budgets, because the company did not prepare The sales budget is counted, and no sales budget is established. production budget and production cost budget. The type of research used is a descriptive method with quantitative methods. The data type is qualitative data and quantitative data, used for data sources, that is, raw data and auxiliary data obtained through interviews, observations, and records. According to the research results, the secondary method is the most suitable method for the company, and the SKP value is 48.18. The prepared sales budget resulted in a sales plan of 5,371 pieces or Rp. 1,068,847,836 a year. The production budget was prepared using the inventory stability method of 5,371 units. Therefore, the company needs a production cost budget of Rp. From June 2021 to May 2022, it is 1,014,602,825.